Chinese small and medium-sized city image communication on Douyin: Algorithmic heuristics and cultural resilience in short-video ecologies - Feixiang Li; Xueqin Peng (PLoS ONE, 2026)
This study examines how Chinese small and medium-sized cities gain visibility and sustain place-based meaning within Douyin’s platformized short-video ecology. Focusing on Shaoguan, Guangdong Province, it analyzes 30 high-interaction Douyin videos published between May 2023 and May 2025 and applies crisp-set Qualitative Comparative Analysis (csQCA) to identify configurations associated with high dissemination performance. The findings suggest that city-related hashtags function as a necessary platform-indexing condition in the sampled archive, while emotional resonance and narrative structure strengthen specific high-impact configurations. Two communicative logics are particularly salient: non-local creators can generate rapid visibility through immersive, fragmented, and affective presentations, whereas locally embedded storytelling can reinforce cultural resilience and place identity. The study contributes to digital urban communication by integrating the Heuristic-Systematic Model with debates on platformization, algorithmic visibility, and digital place branding.